Walking a Fine Line : Public Investment Scaling-Up and Debt Sustainability in Burkina Faso - Kabedi-Mbuyi, Malangu (Departmental Papers; Departmental Paper, 2016)
This paper analyzes the macroeconomics of scaling up public investment in Burkina Faso under alternative financing options, including through foreign aid and a combination of tax adjustment and borrowing. Our findings are twofold: (1) raising official development assistance in line with the Gleneagles agreement provides scope for financing public investment at low cost and would have positive, but somewhat moderate, effects on aggregate output-the growth dividends in the nontradables sector would be partially offset by the Dutch disease in the tradables sector; and (2) the massive investment scaling-up contemplated under Burkina Faso's 'accelerated growth' strategy, while boosting medium- and long-term growth, would lead to unsustainable debt dynamics under a plausible tax adjustment and realistic concessional financing. A more gradual approach to closing Burkina Faso's infrastructure gap is therefore desirable because it would take into account the needed time for the country to address its capacity constraints and to further improve investment efficiency.